Is the perception of physicians based on the type and colour of attire? - Kolasa, Agata; Radziejowska, Zuzanna; Bielak, Alicja; Gryta, Jakub; Iwan, Karolina; Janczewska, Martyna; Kalicka, Maria; Krysa, Tomasz; Szklarz, Magdalena (Quality in Sport, 2023)
Introduction: Patients’ confidence in a physician is influenced by many factors. Recent studies suggest that there’s an association between doctor’s attire and the way patients view physician’s trustworthyness, competence and empathy in various specialties and contexts of care. Along with the developement of medical attire market comes a need to understand how the choice of professional clothes infulences patients’ perceptions. Purpose of the study: The aim of this study was to determine whether patients perception of physician and the confidence in professional skills is determined by the type and colour of doctor’s attire. Materials and methods: We carried out literature search using English based databases (PubMed, Springer, Google Scholar) using key words: physician attire, profesionalism, scrubs, patients perception, psychology of colour. Most recent studies matching this criteria were analysed and those most relevant were picked for this review. Results and conclusions: The assotiation between physician’s attire and patients’ perceptions is complex and depends on numerous factors including age, gender, geographic location and culture, as well as physician’s specialty and context of care. The white coat, despite latest research on it’s role in infections spread, remains an important attribute of a doctor. Physicians who wear white coats are viewed as more trustworthy, knowledgeable, competent and more caring. Colour of scrubs may serve as a valuable hospital personel identification tool. Various colours evoke possitive emotions in patients, navy blue, light blue and green remain the the colours of scrubs that patients perceive as the most professional and appropriate.